No More Muddling Through Mastering Complex Projects in Engineering and Management - Züst, Rainer; Troxler, P. (Springer Netherlands : Imprint: Springer, 2006)
Sustainable solutions require the integration of social and ecological aspects in every planning and decision-making process. This means: analyse the real world and model the problem-situation as a system; understand the needs and objectives of the customers and clients; carefully develop alternative ideas and solutions, as well as evaluate concepts under multidimensional aspects/criteria. In this area Systems Engineering could offer a fruitful approach. Systems Engineering (SE) is a systematic way of thinking and a methodology to guide demanding problem-solving processes in the fields of management and engineering. This book explains the most important principles and elements of Systems Engineering and three planning cases demonstrate the practical application.